Ten years of transformation : macroeconomic lessons - Wyplosz, Charles, 1947- 1947- (Policy research working paper, 2000)
Transition was never going to be easy, even with the highly promising long-run outlook. Not only was the process itself a major theoretical and policy challenge, but politics and economics were bound to interfere. And yet, with some spectacular exceptions, most countries are now on the right track